Allelic loss of 9p21.3 is a prognostic factor in 1p/19q codeleted anaplastic gliomas. (13th October 2015) - Alentorn, Agustí; Dehais, Caroline; Ducray, François; Carpentier, Catherine; Mokhtari, Karima; Figarella-Branger, Dominique; Chinot, Olivier; Cohen-Moyal, Elisabeth; Ramirez, Carole; Loiseau, Hugues; Elouahdani-Hamdi, Selma; Beauchesne, Patrick; et al.
Abstract : Objectives: We aimed to study the potential clinical relevance of 9p allelic loss, with or without copy number variation, in 1p/19q codeleted anaplastic oligodendroglial tumors (AOTs). Methods: This study enrolled 216 patients with 1p/19q codeleted AOT. The prognostic value of 9p allelic loss was investigated using a French nation-wide prospective registry, POLA (prise en charge des tumeurs oligodendrogliales anaplasiques) and high-density single nucleotide polymorphism arrays. We validated our results using the Repository of Molecular Brain Neoplasia Data (REMBRANDT) dataset. Results: The minimal common region of allelic loss in chromosome arm 9p was 9p21.3. Allelic loss of 9p21.3, detected in 41.7% of tumors, was associated with shorter progression-free and overall survival rates in univariate ( p = 0.008 and p < 0.001, respectively) and multivariate analyses ( p = 0.009 and p = 0.009, respectively). This finding was validated in the REMBRANDT dataset in univariate and multivariate analysis ( p = 0.01 and p = 0.01, respectively). Conclusion: Our study highlights a novel potential prognostic biomarker in 1p/19q codeleted AOT. Further prospective studies are warranted to investigate our finding.